The best friend - Fellowes, Jessica (Minotaur Books, 2022)
"Following the intense, toxic friendship of two kindred spirits across their lifetimes, The Best Friend is a dark, suspenseful novel and first standalone from Jessica Fellowes, New York Times bestselling author of the Mitford Murders series and the companion Downton Abbey books. Bella and Kate. Kate and Bella. From childhood they were bosom friends, Bella sensible and cautious, Kate gregarious and just a little dangerous. Yet in spite of their intimacy, their trust is fragile. Men came into their lives and things changed: a black seed was set in the heart of their relationship. Over decades, acts of both cruelty and love ferment until one shocking event tests them more than ever. Neither will escape unscathed. Reminiscent of Elena Ferrante and Sally Rooney, and for readers of Leila Slimani's The Perfect Nanny and Ashley Audrain's The Push, The Best Friend explores the darkest corners of female friendship, a place where loyalty and betrayal intersect with deadly consequences"--